2016
DOI: 10.1186/s40623-016-0380-x
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise tomography in the Naruko/Onikobe volcanic area, NE Japan: implications for geofluids and seismic activity

Abstract: To understand the earthquake generation in volcanic areas, it is important to investigate the presence of geofluids in the uppermost crust. We applied ambient noise tomography to the Naruko/Onikobe volcanic area and constructed a detailed 3-D S-wave velocity (V s ) model using continuous records from a dense seismic network and surrounding stations. The low-velocity zones were found beneath Naruko Volcano, Onikobe Caldera, and Mt. Kurikoma. The low-velocity zone beneath Onikobe Caldera may correspond to a magm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Approximation far-field propagation for Rayleigh is applied to the EGFs to obtain the dispersion curve of phase or group velocity that represents earth structure [6], [7]. The Subsurface imaging using EGF from Rayleigh wave has been successfully applied in upper-crust and [4] volcanic structure investigation in Piton de la Fournaise [8], magma chamber beneath Toba Lake [9], Agung-Batur volcano complex [10], Naruko-Onikobe volcano [11], and Eyjafjallajökull Islandic [12].…”
Section: Methodsmentioning
confidence: 99%
“…Approximation far-field propagation for Rayleigh is applied to the EGFs to obtain the dispersion curve of phase or group velocity that represents earth structure [6], [7]. The Subsurface imaging using EGF from Rayleigh wave has been successfully applied in upper-crust and [4] volcanic structure investigation in Piton de la Fournaise [8], magma chamber beneath Toba Lake [9], Agung-Batur volcano complex [10], Naruko-Onikobe volcano [11], and Eyjafjallajökull Islandic [12].…”
Section: Methodsmentioning
confidence: 99%
“…Due to its features (primarily, continuity over time and space), microseism investigations have broad applications, such as the imaging of the crust and upper mantle by seismic noise tomography [ 181 , 182 ], and the detection of seismic velocity changes in both tectonic and volcanic areas [ 183 , 184 ].…”
Section: Measurement Based On Microseism Observationsmentioning
confidence: 99%
“…American scholar Keefer [10,11] analyzed the data of collapse and landslide hazard caused by earthquakes worldwide, and obtained the distribution patterns of earthquake parameters and collapse and landslide hazard. Japanese scholar Tamura [12,13] analyzed case data of earthquake-induced landslide hazards over the past 100 years in 1978, and obtained the relationship between earthquake parameters such as magnitude and epicenter distance and landslide boundary distance. Huang Yidan [14], a Chinese scholar, and others found that with the increase in earthquake intensity, the development density of collapse geological disasters also increased by interpreting the remote sensing images of the earthquake area and combining with the field survey data.…”
Section: Introductionmentioning
confidence: 99%